2015
DOI: 10.1139/bcb-2015-0057
|View full text |Cite
|
Sign up to set email alerts
|

Does epigenetic dysregulation of pancreatic islets contribute to impaired insulin secretion and type 2 diabetes?

Abstract: β cell dysfunction is central to the development and progression of type 2 diabetes (T2D). T2D develops when β cells are not able to compensate for the increasing demand for insulin caused by insulin resistance. Epigenetic modifications play an important role in establishing and maintaining β cell identity and function in physiological conditions. On the other hand, epigenetic dysregulation can cause a loss of β cell identity, which is characterized by reduced expression of genes that are important for β cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 125 publications
0
28
0
Order By: Relevance
“…Therefore, histone modification enzymes have a highly specific role during the development and differentiation of different pancreatic cells. In addition, studies have shown that the HDAC inhibitor MC1568 can promote the expression of PDX4 and insulin (Dayeh and Ling, 2015 ). These results show that HDAC plays a key role in mediating pancreatic β cell differentiation and development.…”
Section: The Role Of Histone Modification In β Cell Differentiation Amentioning
confidence: 99%
“…Therefore, histone modification enzymes have a highly specific role during the development and differentiation of different pancreatic cells. In addition, studies have shown that the HDAC inhibitor MC1568 can promote the expression of PDX4 and insulin (Dayeh and Ling, 2015 ). These results show that HDAC plays a key role in mediating pancreatic β cell differentiation and development.…”
Section: The Role Of Histone Modification In β Cell Differentiation Amentioning
confidence: 99%
“…Factors that contribute to compromised insulin secretion are not well known and may include epigenetic dysregulation, which is yet to be elucidated. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Second, DNA methylation was measured using DNA extracted from whole blood that was the only accessible type of sample and may not be representative of more disease-relevant tissues for the diseases under study, such as pancreatic cells and adipose tissues. Studies of methylation in obesity or T2D based on disease-relevant tissues such as the skeletal muscle, adipose tissue, or pancreatic islets are interesting but only exist for relatively small studies [ 8 , 13 , 28 , 31 , 32 , 35 , 36 , 41 , 46 ]. Since DNA methylation can be strongly tissue dependent and as our data was obtained from blood samples, for consistency, we only selected methylation probes for replication from EWAS studies that were also performed in the blood.…”
Section: Discussionmentioning
confidence: 99%